Pengaruh Faktor Fundamental Mikro Terhadap Capital Adequacy Ratio (CAR). Studi Pada Bank Umum Indonesia Yang Tercatat di Bursa Efek Indonesia Tahun 2011 – 2015 - . Irdawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
This study aimed to find out the effect of fundamental factors of micro financial ratios including Rentability which was proxied by Return On Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM), Efficiency which was proxied by Operational Efficiency (BOPO), Asset Quality proxied by Non-Performing Loan (NPL), and Liquidity proxied by Loan to Deposit Ratio (LDR), on Capital Adequacy Ratio (CAR) of general Indonesian banks that were registered to Indonesian Stock Exchange. A 5-year period, from 2011 to 2015, was observed by this study. Population of the study included 43 banking companies that were registered to Indonesian Stock Exchange in 2011-2015 period. Samples were determined using the purposive sampling method. Data were analyzed using the multiple linear regression analysis. Data were processed using the Eviews 7. Based on data analysis, it was found that partially ROA, ROE, NIM had a significant effect in CAR, BOPO ratio, NPL, whereas LDR had no effect on CAR. Result of Anova test showed that the value of F statistics was 9.061 with the significance of 0.000. The value of adjusted R-Square was 0.371, which meant that the ability of independent variable to explain dependent variables was 37.1%, whereas the remaining was attributed to other variables beyond the model of this study